Influence of transpersonal brief psychotherapy on depression and anxiety in patients with Crohn’s disease - Acciari, Arlete Silva (Seven Editora, 2023)
Introduction: Crohn’s disease is a chronic illness with continuous and longstanding treatment, being these patients more vulnerable to develop psychological disorders. Objectives: Evaluating the effects of Transpersonal Brief Psychotherapy over anxiety and depression on patients with Crohn’s disease. Method: The sample was composed by 11 Crohn’s disease patients of both sexes and mean age of 40 years old. It was used the clinical method and the procedure consisted of treatment with Transpersonal Brief Psychotherapy based on the theoretical reference of the Transpersonal Integrative Approach with data collection before and after the psychotherapy. The following instruments were used: Sociodemographic Questionnaire, Beck Anxiety Inventory, Beck Depression Inventory and the Crohn’s Disease Activity Index. In order to evaluate the results, it was applied descriptive analysis and the statistical methodology with Wilcoxon test. Results: The procedure turned out to be effective to all instruments (p<0.05) and the most significant result was to depression (-76.8%), followed by anxiety (-62%) and the disease activity (-35%). Conclusion: The Transpersonal Brief Psychotherapy has brought meaningful benefits to patients with Crohn’s disease, reducing the levels of anxiety, depression and the severity of Crohn’s disease and, consequently, it has improved their life quality. DOI:https://doi.org/10.56238/ciênciasaudeestuepesv1-079